Vestibular Function Modulates the Benefit of Hearing Aids in People With Hearing Loss During Static Postural Control. Issue 6 (November 2019) - Maheu, M.; Behtani, L.; Nooristani, M.; Houde, M. S.; Delcenserie, A.; Leroux, T.; Champoux, F.
Abstract : Objectives: To evaluate the influence of auditory cues on postural sway in normal-hearing (NH) individuals, hearing-impaired individuals with vestibular impairment (HIVL), or hearing-impaired (HI) individuals without vestibular impairment. Design: Thirty-two participants received a hearing and a vestibular evaluation (vHIT, oVEMP, cVEMP) and then were separated in to three groups (NH, HI, HIVL). All participants had to stand on a force platform in four postural conditions (A: EO/firm, B: EC/firm, C: EO/Foam, D: EC/Foam) under two auditory conditions, with or without auditory cues. Results: Results revealed that first, there was a significant difference between HIVL and both HI and NH groups in conditions C and D without auditory cues. Second, greater improvement for HIVL compared to NH and HI groups in condition C and D was observed with auditory cues. Finally, somatosensory reliance significantly decreased for the HIVL participants using hearing aids compared to NH and HI. Conclusions: Our results suggest that hearing aids benefit for postural control may be modulated by vestibular function.